ИСТИҚЛОЛДАН КУЧ ОЛГАН КЎНГИЛ - Ибрагимова, Р.И. (SCIENCE and SOCIETY, 2021)
This article tells about the unique thematic features and artistic features of the stories, poems and stories included in the book «Landscapes of the Spirit", one of the works of the poet, publicist Rano Rahmon kyzy, who lived and worked in Karakalpakstan during the years of Independence. Author also analyzes word usage skills, the uniqueness of symbols, and the expression of creative inner experiences.
Keywords: independence; narrative; line; homeland; Aral; motherland; emotion; spirit; soul